2002
DOI: 10.2223/jped.671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early malnutrition and nutritional rehabilitation in rats

Abstract: Objective: to verify the effects of malnutrition and nutritional rehabilitation regarding seizure threshold, body weight and brain weight in rats.Methods: pregnant Wistar rats and their pups were used. Part of the rat pups were submitted to a malnutrition protocol and the rest served as nourished controls. At P15, malnourished and control rats were submitted to status epilepticus induced by flurothyl; and the rehabilitation period started after recovery from seizures. At P30, all rats were submitted to single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 6 publications
4
11
1
10
Order By: Relevance
“…In addition, the body length of the R animals did not approach those of the N animals, even with the long period of dietary change adopted (39 days). Similar findings were demonstrated in Wistar rats and in humans (CASTELUCCI et al, 2002;MONTE, 2000;NUNES et al, 2002). These observations have been attributed to changes in the cell proliferation of bone marrow precursors, which act in response to growth stimuli, causing a loss in development, precisely during the period in which the animal needs the most protein intake (NAKAJIMA et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In addition, the body length of the R animals did not approach those of the N animals, even with the long period of dietary change adopted (39 days). Similar findings were demonstrated in Wistar rats and in humans (CASTELUCCI et al, 2002;MONTE, 2000;NUNES et al, 2002). These observations have been attributed to changes in the cell proliferation of bone marrow precursors, which act in response to growth stimuli, causing a loss in development, precisely during the period in which the animal needs the most protein intake (NAKAJIMA et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…Low body weight and growth retardation are the primary reported data in undernourishment animals or humans (MUGERWA, 1971;NUNES et al, 2002;ROMANI;LIRA, 2004;WATERLOW, 1997); when the malnutrition is imposed on the mother this affects especially the intrauterine phase (BRETON et al, 2009;COUPÉ et al, 2009). This data is confirmed in the experimental model used, which showed that undernourished animals had the lowest body weight, in addition to the lowest intake of food and water, and the lowest excretion of urine and feces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After inducing malnutrition in rats, Holloway et al [12] found smaller, undernourished, lighter pups with retarded development (opening of eyes and outer ear). Nunes et al [25] submitted rats to low PCM during their growth, resulting in animals with smaller size and lower weight than animals with a normal diet. Corroborating the findings of these authors, the present study found significant differences in the weight of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…When pro teins fail to play their struc tu ral and enzy ma tic role, a state of meta bo lic imba lan ce sets in and ane mia, hypo vi ta mi no sis and pro tein-energy mal nu tri tion may deve lop in the indivi dual, this lat ter con di tion being one of the fore most social pro blems pre va lent in Brazil. 10 Protein-energy mal nu tri tion (PEM) results from ina de qua te diet and is cha rac te ri zed by energy deficiency due to a reduc tion in the inta ke of all macro nutrients and often many micro nu trients. Clinically, PEM is clas si fied into three major syndro mes: maras mus, kwas hior kor or maras mic kwas hior kor, a com bi na tion of the two.…”
Section: Introductionmentioning
confidence: 99%